Comparison of antimicrobial efficacy of eravacycline and tigecycline against clinical isolates of Streptococcus agalactiae in China: In vitro activity, heteroresistance, and cross-resistance. (December 2020) - Li, Peiyu; Wei, Ying; Li, Guiqiu; Cheng, Hang; Xu, Zhichao; Yu, Zhijian; Deng, Qiwen; Shi, Yiyi
Abstract: Aims: The aims of this study were to compare the antimicrobial efficacy of Eravacycline (Erava) versus tigecycline (Tig) in vitro against clinical isolates of S. agalactiae from China and further to evaluate the heteroresistance risk and resistance mechanisms of Erava. Methods: 162 clinical isolates of S. agalactiae were collected retrospectively and the minimal inhibitory concentrations (MICs) of Erava and Tig were determined by agar dilution. Moreover, Tetracycline (Tet) specific resistance genes, genetic mutations in Tet target sites, and sequence types (ST) profiles of clinical isolates of S. agalactiae were investigated with polymerase chain reaction (PCR) experiments. The heteroresistance frequency of Erava and Tig in S. agalactiae was analyzed by population analysis profiling. Furthermore, the resistance mechanisms of both Erava and Tig were investigated in antibiotic-induced resistant S. agalactiae isolates in vitro . Results: The MIC values of Erava and Tig were shown with ≤0.25 mg/L and ≤0.5 mg/L, respectively, against clinical S. agalactiae isolates, including that harboring the Tet-specific resistance genes tet (K), tet (M), or tet (O). The heteroresistance frequency of Tig among the clinical isolates of S. agalactiae was 1.84% (3/162), whereas no positive Erava heteroresistance was found. The enhanced MIC values of both Erava and Tig in the heteroresistance-derivative S. agalactiae clones could be reversed by the efflux pump inhibition experiments. Genetic mutations affecting 30S ribosome units (16SrRNA copies or 30S ribosome protein S10) could result in the cross resistance toward Erava and Tig in the antibiotic-induced resistant S. agalactiae isolates in vitro . Conclusions: Erava MIC values were nearly half of that of Tig against the clinical isolates of S. agalactiae from China and genetic mutations in the 30S ribosome units of Tet target sites (16SrRNA copies or 30S ribosome protein S10) participated in the resistance evolution of both Erava and Tig under the antibiotic pressure. Highlights: Erava exhibited robust in vitro antibacterial activity with MIC value ≤ 0.25mg/L against clinical isolates of S. agalactiae. The heteroresistance frequency of tigecycline was 1.84% (3/162), whereas no Erava heteroresistance was found. The MICs of Erava and Tig in the heteroresistance-derivative S. agalactiae clones were reversed by efflux pump inhibition. The Lys57Arg mutation in the 30S ribosomal protein S10 was commonly found in the antibiotic-induced resistant S. agalactiae .